Advances in applied mechanics - Bordas, Stephane; Balint, Daniel S. (Elsevier Academic Press, 2016)
Advances in Applied Mechanics draws together recent, significant advances in various topics in applied mechanics. Published since 1948, the book aims to provide authoritative review articles on topics in the mechanical sciences. While the book is ideal for scientists and engineers working in various branches of mechanics, it is also beneficial to professionals who use the results of investigations in mechanics in various applications, such as aerospace, chemical, civil, environmental, mechanical, and nuclear engineering.